Family Welfare and School Readiness in Grade 1 Elementary School Students - Ciciria Fadillah; Lely Ika Mariyati (Universitas Muhammadiyah Sidoarjo, 2022)
This research was conducted because of the phenomenon of the readiness of children to enter elementary school carried out by grade 1 elementary school students in Trompoasri village. The purpose of the study was to determine the relationship between family well-being and the readiness of children to enter elementary school by 1st grade elementary school children. This type of research is correlational quantitative research. The variables in this study were family well being as the independent variable and the readiness of children to enter elementary school as the dependent variable. The population in this study was 57 students. The sample in this study amounted to 53 students from a total population of 57 students. Sampling was carried out using a non-probability sampling technique in the form of saturated sampling. The hypothesis proposed is that there is a positive relationship between family well-being and the readiness of children to enter elementary school in grade 1 elementary school children.Data analysis using Pearson product moment correlation technique with the help of SPSS 26.0 for windows program. Based on the results of the analysis of this study, the correlation coefficient is 0.295 with a significance value (0.044 < 0.05), meaning that there is a positive relationship between family well-being and the readiness of children to enter elementary school for grade 1 elementary school children in Trompoasri village. The higher the family well being, the higher the readiness of children to enter elementary school, and vice versa, the lower the family well being, the lower the readiness of children to enter elementary school.